Reorienting the focus from an individual to a community-level lens to improve the pathways through care for early psychosis in the United States - Oladunni Oluwoye; Arundati Nagendra; Liat S. Kriegel; Deidre M. Anglin; Maria M. Santos; Steven R. López (Elsevier, 2023)
The implementation of coordinated specialty care in the U.S. over the past decade has led to the improvements of clinical and functional outcomes among individuals in the early stages of psychosis. While there have been advancements in the delivery of early intervention services for psychosis, it has almost exclusively focused on short-term change at the individual level. In light of these advancements, research has identified gaps in access to care and delivery of services that are driven by different levels of determinants and have the biggest impact on historically excluded groups (e.g., ethnoracial minoritized communities). Interventions or efforts that place an emphasis on community level (structural or sociocultural) factors and how they may influence pathways to care and through care, specifically for those who have been historically excluded, have largely been missing from the design, dissemination and implementation of early psychosis services. The present paper uses a structural violence framework to review current evidence related to pathways to care for early psychosis and the physical/built environment and conditions (e.g., urbanicity, residential instability) and formal and informal community resources. Suggestions on future directions are also provided, that focus on enriching communities and creating sustainable change that spans from pathways leading to care to 'recovery.' In all, this lays the groundwork for a proposed paradigm shift in research and practice that encompasses the need for an emphasis on structural competency and community-driven approaches.